IMPROVING EIGHTH GRADERS’ READING COMPREHENSION ON DESCRIPTIVE TEXT THROUGH PORPE STRATEGY - Dewi Ayu Ningrat; Heru Setiawan (FKIP Universitas Tridinanti, 2022)
This study was aimed to find out whether there were any significant differences in reading comprehension on descriptive text through PORPE (predict, organize, rehearse, practice, evaluate) strategy and those who were not. There were 66 students of eighth graders of SMP Negeri 13 Palembang were involved in this study as the sample, the experimental group consisted of 33 students and the control group consisted of 33 students. The method of this study was quantitavie method with a quasi experimental design. The experimental group were taught by using PORPE (predict, organize, rehearse, practice, evaluate) strategy. The control group were taught by using discussion strategy. The result of paired sample T-Test in control group showed the value of t-obtained was 6.508 at the significance level 0.000 with degree of freedom was 33 (1.669) and the significance (2 tailed) was lower than 0.05. The result of paired sample T-Test in experimental group showed the value of t-obtained was 5.003 at the significance level 0.000 with degree of freedom was 33 (1.669) and the significance (2 tailed) was lower than 0.05. The result of independent t-test from experimental and control group shown that t-obtained was 1.742 and it was higher than t-table 1.669.